Comparison of single-dose tetracycline hydrochloride to conventional therapy of urinary tract infections. - Rosenstock, J (1985)
Sixty-two women with signs and symptoms compatible with lower urinary tract infections were randomized to receive single-dose tetracycline (2 g), multi-dose tetracycline (500 mg four times per day for 10 days), or single-dose amoxicillin (3 g). Urine cultures were obtained upon entry into the study and on days 4, 14, and 28 after therapy. Single-dose tetracycline cured 12 of 16 (75%) of women with documented urinary tract infections, compared with 15 of 16 (94%) in the multi-dose tetracycline group and 7 of 13 (54%) receiving single-dose amoxicillin. Mild nausea in 3 of 20 patients (15%) was the only complication in the single-dose tetracycline group. Two grams of single-dose tetracycline is as effective as other reported regimens regardless of the susceptibility of the initial pathogen and has minimal toxicity.